Ethical dimensions of administrative power - Rajan, Amitabh (SAGE Publishing, 2021)
This insightful textbook explores the use and application of ethics in contemporary governance and suggests necessary reforms. Discussions on administrative ethics need an interdisciplinary approach involving the fields of political science, law, economics, sociology, management and philosophy. Combining the perspectives from these fields, this textbook analyses their applicability and usefulness in everyday practices in governance, covering its five cardinal virtues-prudence, transparency, discourse, justice and accountability. The textbook highlights ethical challenges in aspects of status recognition, oppression, empowerment, social care, public financing, environment protection and others in today's interconnected world. It delves into the dynamics of administrative power in democracies and showcases how the misuse of power can be controlled through a discourse of ethics in law and governance. Key Features Practical insights and examples from around the world to connect the younger generation with the role of ethics in administration and governance Plethora of teaching-learning tools such as illustrative case studies, notes on administrative thinkers, glossary of key concepts and select reading list Chapters aided by study questions for self-assessment, appendices on key documents used in governance ethics and a list of landmark instances in administrative history"--